The mediating effects of ego-resilience in the relationship between organizational support and resistance to change - Ferreira, A. I.; Cardoso, C.; Braun, T. (Baltic Journal of Management, 2018)
Purpose This study drew upon conservation of resources and organizational support theory to develop a deeper understanding of the antecedents of affective and behavioral reactions to change processes. The purpose of this paper is to construct a theoretical framework based on previous findings of change management research to suggest that the relationship between organizational support and resistance to change is mediated by ego-resilience. This framework was then validated empirically. Design/methodology/approach To test this model, the mediation relationship was examined using regression analysis with bootstrapping. The sample consisted of 323 employees from private and public organizations. Findings The results confirmed that the relationship between organizational support and affective and behavioral reactions to imposed change is mediated by ego-resilience. The theoretical model was thus validated for use in future research. Research limitations/implications This study’s findings have implications for organizations regarding how managers guide their employees through change processes. The research’s limitations arise from the use of convenience non-probability sampling and cross-sectional, self-reported data, which only allow for a tentative generalizability of the results. Originality/value The findings show that organizational change processes are affected by factors on both the individual (i.e. ego-resilience) and organizational level (i.e. organizational support). This study’s results thus provide empirical support for the conclusion that ego-resilience mediates the indirect relationship between organizational support and employees’ resistance to change.